Effects of Oxide Ions on the Electrodeposition Process of Silicon in Molten Fluorides. Issue 13 (13th August 2019) - Suzuki, Yuta; Inoue, Yosuke; Yokota, Masayuki; Goto, Takuya
Abstract : We studied the effects of O 2− ions on the coordination structure of Si ions and the electrodeposition process of Si films in molten fluorides using SiO2 powder (as a source of Si) and Li2 O (as a source of O 2− ). High-temperature Raman spectroscopic data revealed that the dissolution of SiO2 in molten KF, LiF-KF, and LiF-NaF-KF without Li2 O was proceeded by the formation of silicate ions, with the [Si2 O5 ] 2− ion acting as the dominant species. On the other hand, when 3.0 mol% Li2 O was added to molten LiF-KF and LiF-NaF-KF, the intensity of Raman band due to [SiO3 F] 3− ion was increased compared to that without Li2 O system, which indicated that the O 2− ions could cause breakage of Si-O-Si bonds of SiO2 or [Si2 O5 ] 2− ions. Furthermore, the reduction currents, attributed to the reduction of Si ions, increased significantly by the addition of Li2 O; moreover, the thickness and current efficiency of the electrodeposited polycrystalline Si layer prepared by potentiostatic electrolysis was improved. These results indicated that the O 2− ions can change the coordination structure of Si ions in molten fluorides and that the design of the molten salts bath is a key technology for fabricating high-quality Si layers with high current efficiency.